Competency Profile of Project Team Members – Interplay with Team Dynamics and Project Success - Ana Juras (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
In contemporary business environment, in which learning and knowledge are considered as the only sustainable competitive advantage of modern organisations, and there is a trend of growing reliance on project type of teams' and organizations' functioning, competencies of project team members are becoming more important than ever. By integrating competencies of fundamental managerial functions and competencies of project management's knowledge areas, this paper investigates the nature of competency profile of project team members, as well as its main effects on project. Established competency profile of project team members is analysed in relation to project team dynamics and project success. The mediating role of project team dynamics in the effect of competency profile of project team members on project success is also investigated in the paper. Cross-sectoral empirical research was conducted during the spring of 2018, through which data from 83 project team members was collected via questionnaire. Collected data was enrolled and processed in SPSS 23.0, with addition of Hayes' (2018) PROCESS Macro for SPSS - v3.2. Results obtained through descriptive, bivariate and multivariate analysis led to very interesting insights and inferences, especially when considering the cluster analysis' and mediation effects' results related to the interplay of project team members' competency profile, project team dynamics and project success.
Keywords: 650; competencies; competency profile; project team member; project team dynamics; project success